Countering Democratic Disruption Amid The Disinformation Phenomenon Through Artificial Intelligence (AI) In Public Sector - R.A. Yashinta Sekarwangi Mega (Jurnal Manajemen Pelayanan Publik, 2023)
In today’s era, artificial intelligence (AI) has emerged as a groundbreaking technology that plays a vital role in shaping societies and revolutionizing various sectors. Many democratic countries are currently exposed to a variety of false information spread through social media. In politics, disinformation is often associated with the efforts of a particular movement or party to mobilize supporters against the moral order. The spread of disinformation causes the emergence of legitimacy problems in many democratic countries.   Citizen confidence in the credibility of official information in the news started to decline and shifts to alternative sources of information such as social media. Several countries that adhere to a democratic system make various efforts to fight the phenomenon of disinformation. The origins of the problems research want to examine the use of AI technology as an effort to overcome the spread of disinformation on social media. Furthermore, this research examines the challenges posed by AI disinformation and highlights several measures that democratic governments should adopt to mitigate its impacts. In summary, prioritizing the fight against disinformation in democratic countries is imperative to safeguard the integrity of democratic processes, enhance societal resilience, and foster an informed citizenry capable of making critical decisions for the collective benefit of the nation.